2010
DOI: 10.1590/s1415-47572010005000056
|View full text |Cite
|
Sign up to set email alerts
|

Replication of TCF7L2 rs7903146 association with type 2 diabetes in an Iranian population

Abstract: The transcription factor 7-like 2 gene (TCF7L2) rs7903146 T allele is constantly associated with Type 2 diabetes in various populations and ethnic groups. Nevertheless, this has not been observed in two studies involving Arab populations. The aim of the present study was to investigate the association between TCF7L2 rs7903146 in an Iranian population. Type 2 diabetes patients (N = 258) and normal healthy control subjects (N = 168) from the same area, were examined. The ARMS- PCR (Amplification Refractory Mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…These three SNPs, individually and/or as a group, were found to be associated with T2DM in a wide spectrum of world populations: Finnish [19], Amish [20], U.S [21], Polish [22], Scandinavian [23], Chinese [24], Brazil [25], Japanese[26][28], Swedish [29], U.K [30], Dutch [31], Palestinian [32], Iranian [33], [34], Arab [35], Tunisian [36], Persian [37] as well as Indian populations [13][17]. Of the three SNPs, rs7903146 is the most consistent in several GWAS studies [5], [38][45] as well as most replicated variant of TCF7L2.…”
Section: Introductionmentioning
confidence: 99%
“…These three SNPs, individually and/or as a group, were found to be associated with T2DM in a wide spectrum of world populations: Finnish [19], Amish [20], U.S [21], Polish [22], Scandinavian [23], Chinese [24], Brazil [25], Japanese[26][28], Swedish [29], U.K [30], Dutch [31], Palestinian [32], Iranian [33], [34], Arab [35], Tunisian [36], Persian [37] as well as Indian populations [13][17]. Of the three SNPs, rs7903146 is the most consistent in several GWAS studies [5], [38][45] as well as most replicated variant of TCF7L2.…”
Section: Introductionmentioning
confidence: 99%
“…Most published epidemiological studies have placed emphasis on rs7903146 (C/T) and rs12255372 (G/T) variations (Luo et al , 2009; Tong et al , 2009), with the consequential association of rs7903146 TCF7L2 polymorphism with T2DM (Amoli et al , 2010). …”
Section: Introductionmentioning
confidence: 99%
“…The results showed that GC and CC genotypes of rs11196205 of TCF7L2 gene were strongly associated with T2D as risk factor, and C allele of this gene SNP (rs4132670) was not associated with T2D. However, previous studies have proved that rs7903146C/T polymorphism of TCF7L2 is associated with T2D in different ethnic populations (12)(13)(14)(15). There is little data regarding the role of TCF7L2 polymorphism (rs11196205 and rs4132670), especially rs4132670 polymorphism.…”
Section: Discussionmentioning
confidence: 94%